Paint handling in Leonardo’s Mona Lisa: guides to a reconstruction - Sandra Šustić (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art, 2018)
Mona Lisa, the precious legacy of Leonardo da Vinci, represents a zenith of methodological innovations in painting. How the painter managed to obtain such delicacy of the tonal transitions still occupies the mind of contemporary art researchers. Based on published results of scientific analyses performed on the painting and relying on historical sources, a copy of the painting was made using materials that were identical or at least equivalent to the ones Leonardo used. This paper is an effort to provide an idea of the built-up of the paint layers at various stages as the painting evolved. The author discusses the detailed and painstaking method used by the painter at each step of the creation of the painting to obtain sfumato effect.